The cost of infection: Argulus foliaceus and its impact on the swimming performance of the three-spined stickleback (Gasterosteus aculeatus). Issue 147 (24th October 2018) - Stewart, A.; Hunt, R.; Mitchell, R.; Muhawenimana, V.; Wilson, C. A. M. E.; Jackson, J. A.; Cable, J.
Abstract : For fish, there can be multiple consequences of parasitic infections, including the physical impacts on swimming and the pathological costs of infection. This study used the three-spined stickleback ( Gasterosteus aculeatus ) and the ectoparasitic fish louse, Argulus foliaceus, to assess both physical (including form drag and mass) and pathological effects of infection. Both sustained (prolonged swimming within an open channel flume) and burst (C-start) swimming performance were measured on individual fish before (trials 1–2) and after infection (trials 3–5). Experimental infection occurred shortly before the third trial, when the physical impacts of infection could be separated from any subsequent pathology as transmission of adult parasites causes instantaneous drag effects prior to observable pathology. Despite the relatively large size of the parasite and corresponding increase in hydrodynamic drag for the host, there were no observable physical effects of infection on either sustained or burst host swimming. By contrast, parasite-induced pathology is the most probable explanation for reduced swimming performance across both tests. All sticklebacks displayed a preference for flow refugia, swimming in low-velocity regions of the flume, and this preference increased with both flow rate and infection time. This study suggests that even with large, physically demanding parasites their induced pathology is of greater concern than direct physical impact.